2001
DOI: 10.1093/humrep/16.3.441
|View full text |Cite
|
Sign up to set email alerts
|

Physiological concentrations of albumin stimulate chorionic gonadotrophin and placental lactogen release from human term placental explants

Abstract: This study investigates whether albumin, a major plasma protein in direct contact with the trophoblast in vivo, can modulate human chorionic gonadotrophin (HCG) and human placental lactogen (HPL) releases from placental explants. Incubating explants with a near physiological, i.e. 5%, concentration of human or bovine albumin during 30 min increased HCG and HPL release by at least 150%. This albumin effect was not mediated by any difference in hormone adsorption onto glass surfaces. In contrast to the sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Since hCG release from tissue perfused with bupropion and in absence of HSA was not different from control placentas, it could be attributed to the effect of the added protein. Moreover, the increase in hCG release in presence of HSA observed in this report is in agreement with that reported for albumin stimulation of release of the hormone from term trophoblast explants in culture [21]. …”
Section: Resultssupporting
confidence: 92%
“…Since hCG release from tissue perfused with bupropion and in absence of HSA was not different from control placentas, it could be attributed to the effect of the added protein. Moreover, the increase in hCG release in presence of HSA observed in this report is in agreement with that reported for albumin stimulation of release of the hormone from term trophoblast explants in culture [21]. …”
Section: Resultssupporting
confidence: 92%
“…Albumin has also been shown to stimulate the release of placental lactogen and human chorionic gonadotrophin from term placental explants (Cirelli et al 2001). The results of these studies and its presence as a common protein in trophoblastderived exosomes, lend support to the notion that albumin may contribute to the functions of exosomes.…”
Section: Proteinsmentioning
confidence: 64%
“…After the cells reached confluence, the media were replaced with 2 mL of control (4% fatty-acid free BSA - bovine serum albumin) or FFA (0.7 mM palmitate, oleate, or linoleate with 4% BSA) media and changed every 24 hrs. The BSA level used was close to physiological levels [28]. 0.7 mM FFAs was employed in this study because the plasma FFA levels in obese and type 2 diabetic patients have been reported to be approximately this level [29, 30, 31, 32].…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%